Tipologi Daerah Kabupaten dan Kota di Wilayah Jawa Bagian Barat - Endang Setiasih (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2008)
Economic potency in regions of west java regions is interesting to analyze. On 2000 to 2004, these regions had referred to structural economic changing which signed by the changing of its some secondary economic sectors share. Nevertheless, regional typology shows the income disparities among the regency on this regions. Especially, the regions with low per capita income and coincide with low economic growth should need to concern. Without right and wise policy, these regions will always left behind from the other regions if they are compared to the regions that have better typology. Key words: economic potency, regional typology, income disparities